PREVALENCIA DE Trypanosoma vivax EN BOVINOS DE SELVA ALTA EN LA PROVINCIA DE CHACHAPOYAS, AMAZONAS. - Tafur T., Manuel (2002)
The aim of the present research was to determine the prevalence of Trypanosoma vivax in cattle of the province of Chachapoyas, located in the tropics of Perú. A total of 270 blood smears from 270 criollos, Holstein, Brown Swiss and Zebu crosses were evaluated. The prevalence of T. viva.x was 1 O.O± 3 .4% (27 /270) without differences between sexes (P>0.05). None of the positive animals showed clinical signs related to trypanosomosis. The study reported for the first time the presence of T. viva.x in the (Chachapoyas province. Further studies in this and other tropical regions using more sensitive techniques are recommended.